2010
DOI: 10.1097/yct.0b013e3181c3aef3
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Delayed Onset of Threatened Premature Labor in Association With Electroconvulsive Therapy in the Third Trimester of Pregnancy

Abstract: Electroconvulsive therapy (ECT) is recommended by the American Psychiatric Association Task Force on ECT as a safe and effective treatment of depression throughout pregnancy. We report here administration of ECT in the third trimester of pregnancy in a 33-year-old patient with severe bipolar depression. The patient had a good antidepressant response to ECT. She experienced, however, delayed onset premature uterine contractions at home after her sixth session of ECT (10 hours post-ECT administration). After rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…(See summary of findings table, Appendix 3 ). UL placement of electrodes was noted in six studies (Balki et al 2006 ; Gahr et al 2012 ; Pesiridou et al 2010 ; Varan et al 1985 ; Wise et al 1984 ; Yellowlees and Page 1990 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(See summary of findings table, Appendix 3 ). UL placement of electrodes was noted in six studies (Balki et al 2006 ; Gahr et al 2012 ; Pesiridou et al 2010 ; Varan et al 1985 ; Wise et al 1984 ; Yellowlees and Page 1990 ).…”
Section: Resultsmentioning
confidence: 99%
“… Medication: Quiatipine and lamotrigine medication in 3rd trimester. Cardiotocography not used, since authors claim information from this to be limited before 24 GW Pesiridou et al ( 2010 ) Case USA 33 years, P3, GW 30–32 Bipolar II, alcohol and cocaine abuse, borderline personality disorder 6 UL Brief pulse ECT Maternal position: left hip lateral tilt Device: Mecta spectrum 5000Q 60-Hz 15 s seizures first then etomidate substitution increased to 38–45 s Anesthesia: Methohexital 170 mg and muscle relaxant succinylchlorine 100 mg 10 h after ECT session 6 painful contractions, further intermittent contractions until spontaneous birth at 37 GW Baby ok Apgar 9 Serim et al ( 2010 ) Case Turkey 16.5 years, P1, GW 29 (at admission), GW 31 (at ECT start) Major depression with psychotic features (HDRS score 32) 10 ECTs (lasting 30 s or more) BL (bitemporal) Brief pulse wave Device: Thyamtron System IV Anesthesia. Propofol 1 mg/kg and muscle relaxant rocuronium.…”
Section: Appendixmentioning
confidence: 99%
“…Fetal bradyarrhythmia is the most common problem in the fetus caused by ECT [ A change of anesthetic agent from methohexital to propofol attenuated the seizure duration resulting in the elimination of further events of fetal cardiac deceleration and a successful outcome for both mother and fetus [81] Gahr et al to rTMS [82] Salzbrenner et al [85] O'Reardon et al Mother: cesarean delivery Fetus: no complications ECT was effective and safe for treating severe major depression during pregnancy [86] Pesiridou et al ECT during the third trimester of pregnancy may be delayed. Patients and treatment team need to be aware of this possibility, particularly when ECT is conducted on an outpatient basis [87] Ghanizadeh et al Ceccaldi et al [90] Pinette et al ECT is effective and safe [94] DeBattista et al Fukuchi et al Inhalation anesthesia is beneficial for ECT in the last stage of pregnancy to reduce uterine contractions caused by potential uterine relaxation effect of anesthetics [97] Bhatia et al ECT during pregnancy improves maternal condition and does not adversely affect fetal wellbeing [102] Sherer et al Mother: no complications Fetus: no complications ECT was highly effective and careful monitoring of both the mother and the fetus demonstrated that this was a safe procedure [103] Griffiths et al Transient fetal heart rate decreases probably result mainly from hypoxia [68]. The electroconvulsive current does not pass through the uterus [69,70], and so other physiological and pathophysiological factors have to be considered as causes for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Electric shocks affecting neurons and chemicals in the brain lead to short and controlled seizures which have excellent effects in various neurological disorders [30]. However, treating ECT with pregnant women shows various adverse effects including vaginal bleeding and miscarriage [31], uterine contraction [32], abdominal pain [33], and Preeclampsia [34].…”
Section: Introductionmentioning
confidence: 99%